Apokalipszis és ébredések - Ertüngealp, Alpaslan (Kultúratudományi Szemle, 2022)
Apocalypse and awakenings Alpaslan Ertüngealp Apocalypse and awakenings. This paper presents two conflicting meanings of apocalypse, one originating from the original literary meaning in Greek and the other derived from eschatological writings and visions of Christian and other religions. Apocalypse is presented here as a necessary means for the survival of the human race, that has innate destructive instincts and desires, which without the creation of the concept of apocalypse could have led to the self-extinction of the human race.